146k views
2 votes
Identify the properties used for the first two steps in simplifying 6ab2 + 4a2b – 3ab2 + 3a2b – 2a2b2.

2 Answers

3 votes
The expression
6ab^2+4a^2b-3ab^2+3a^2b-2a^2b^2 has two similar pairs of conjunctions.

1. Rewrite this expression as

6ab^2+4a^2b-3ab^2+3a^2b-2a^2b^2=

=(6ab^2-3ab^2)+(4a^2b+3a^2b)-2a^2b^2
and then
2. add the similar conjunctions


(6ab^2-3ab^2)+(4a^2b+3a^2b)-2a^2b^2=3ab^2+7a^2b-2a^2b^2.



User BartusZak
by
5.7k points
4 votes

Answer:

commutative property of addition

distributive property

Explanation:

Identify the properties used for the first two steps in simplifying 6ab2 + 4a2b – 3ab2 + 3a2b – 2a2b2.

6ab2+4a2b-3ab2+3a2b-2a2b2 = 4a2b+3a2b-3ab2+6ab2-2a2b2 -commutative property of addition

= (4+3)a2b+(-3+6)ab2-2a2b2

= 7a2b+3ab2-2a2b2 -distributive property

User Ranjith King
by
5.3k points